Analysis of the aspects of residual stresses quantification performed by 3D DIC combined with standardized hole-drilling method. (April 2019) - Hagara, Martin; Trebuňa, František; Pástor, Miroslav; Huňady, Róbert; Lengvarský, Pavol
Highlights: Described aspects of 2D and 3D DIC analysis in the surrounding of a drilled hole. Dependence between the facet size and the smoothing level is determined. For quantification of the uniform residual stresses standard DIC system is used. The obtained results' correctness is verified using strain gage instruments. Abstract: Recently, non-contact optical methods are increasingly used to residual stresses quantification. The main reason is that the full-field aspect provides a rich source of data in relatively short time. However, the optical devices allowing such measurements are usually designed specially just for such type of analysis. The paper describes the possibility of using standard digital image correlation (DIC) system combined with the hole-drilling method for quantification of residual stresses. The residual stresses are determined due to a methodology given in standard ASTM E837-13a. The precision of the results obtained by DIC depends on many factors, e.g. experience of the experimenters, quality of the acquired images, calibration parameters and proper setting of correlation parameters. In the first part of paper, the authors describe the experiments leading to a comparison of errors incident possibly by strain analysis performed in the surrounding of the hole by single or stereo camera system. As the obtained results prefer the use of 3D measurement, the following parts of the paper present the work with stereo camera system. The authors point to the importance of correct choice of facet size and corresponding smoothing of strains acquired in the surrounding of a drilled hole. For that purpose, two experiments were performed, the results of which were compared with the results obtained by finite element analysis, whereby one of the used numerical models was verified by experimental analysis using transmission photoelasticity method. The last part of paper deals with the quantification of simulated uniform stresses by means of hole-drilling method. In order to prove the correctness of correlation parameters proposed after the aforementioned experiments, the measurement of artificially established residual stresses was performed simultaneously using strain gage instruments and digital image correlation system. The obtained results confirm that under some conditions, described in the conclusions, it is possible to realize quantification of residual stresses also by standard digital image correlation method with high accuracy. The authors suppose that described methodology should not be insignificant without the use of the applied correlation system and after implementation can be used in general for any correlation system.